2017
DOI: 10.1111/ane.12773
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency rTMS of the unaffected hemisphere in stroke patients: A systematic review

Abstract: The aim of this review was to summarize the evidence for the effectiveness of low-frequency (LF) repetitive transcranial magnetic stimulation (rTMS) over the unaffected hemisphere in promoting functional recovery after stroke. We performed a systematic search of the studies using LF-rTMS over the contralesional hemisphere in stroke patients and reviewed the 67 identified articles. The studies have been gathered together according to the time interval that had elapsed between the stroke onset and the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 122 publications
0
36
0
1
Order By: Relevance
“…In a systematic review, Sebastianelli et al found that low-frequency rTMS over unaffected hemisphere may have therapeutic utility after stroke (29). Recently McIntyre et al evaluated the effectiveness of rTMS in improving spasticity after stroke (30). Using Modified Ashworth Scale as main outcome 10 studies met the inclusion criteria: two randomized control trials and eight uncontrolled pre-post studies.…”
Section: The Application Of Transcranial Magnetic Stimulation In Stromentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, Sebastianelli et al found that low-frequency rTMS over unaffected hemisphere may have therapeutic utility after stroke (29). Recently McIntyre et al evaluated the effectiveness of rTMS in improving spasticity after stroke (30). Using Modified Ashworth Scale as main outcome 10 studies met the inclusion criteria: two randomized control trials and eight uncontrolled pre-post studies.…”
Section: The Application Of Transcranial Magnetic Stimulation In Stromentioning
confidence: 99%
“…In the uncontrolled pre-post studies they found significant improvements in Modified Ashworth Scale for elbow, wrist, and finger flexors. However the two available RCTs failed to find a significant rTMS treatment effect on Modified Ashworth Scale for the wrist (30). Zhang et al evaluated the short-and long-term effects of rTMS on upper limb recovery after stroke and they show that 5-session rTMS and intermittent theta burst stimulation in the acute phase of stroke significantly improved short-term and long-term manual dexterity (31).…”
Section: The Application Of Transcranial Magnetic Stimulation In Stromentioning
confidence: 99%
“…Several studies indicated that inhibitory rTMS over the contralesional inferior frontal gyrus improves recovery from poststroke non-fluent aphasia by reducing right hemisphere hyperactivity and transcallosal inhibition on left Broca's area [for a review: (12,13)]. With small left hemisphere lesions, perilesional regions are recruited to subserve the recovery of language function.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that post-stroke low-frequency rTMS over the motor cortex of the unaffected hemisphere helps patients recover their affected hand motor functions [ 9 - 11 ]. In a recently published guideline, stimulating the unaffected motor cortex with low-frequency rTMS in the acute to chronic phase of stroke was methodologically sufficient to reach a Level B or ‘probable efficacy’ recommendation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%